Compensation of machine tool spindle error motions in the radial direction for accurate monitoring of cutting forces utilizing sensitive displacement sensors - Sarhan, Ahmed Aly Diaa Mohammed; Hassan, M.A.; Matsubara, A.; Abd Shukor, Mohd Hamdi (Springer, 2011)
This paper deals with the cutting force monitoring for intelligent end milling operations. The authors have employed displacement sensors to monitor the cutting forces, as they are cheap and small enough to be built in the spindle structure. A monitoring method, which utilizes sensitive displacement sensors, is discussed. The sensors are installed in X Y directions near the front bearings of the spindle, to detect the small displacements of a spindle caused by cutting forces. Monitoring tests are carried out under end milling operations and the cutting forces are estimated from the displacement signals by the simple signal processing technique. However, as the displacement sensor measures the variation of the gap size between the sensor head and the target surface, it also records displacements due to error motion of a spindle's axis of rotation in radial direction and roundness errors of the target surface. By comparing the cutting force estimated from displacement sensors with the cutting force measured by using a dynamometer, the machine tool spindle error motions is investigated, and its compensation scheme is proposed. The test results show that the monitoring system is reliable for the adaptive control of machining accuracy for end milling process